2020
DOI: 10.5812/jhealthscope.95588
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Educational Program Based on the BASNEF Model on Knowledge and Self-Care Behaviors of Patients with Hypertension

Abstract: Background: Hypertension is an important health problem that can be controlled by self-care. Objectives: The present study aimed to determine the impact of an educational program based (BASNEF) model on knowledge and self-care behaviors for hypertensive patients in Bastak, Iran. Methods: This quasi-experimental study was performed on 180 patients with hypertension who were admitted to health centers of the Bastak city. The participants were randomly assigned to intervention (n = 90) and control (n = 90) groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Systolic and diastolic blood pressure control based on the BAZNEF model,[ 42 44 ] modifications in blood pressure (BP), and body mass index[ 36 ] confirmed the effect of theory-based intervention on clinical outcomes.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Systolic and diastolic blood pressure control based on the BAZNEF model,[ 42 44 ] modifications in blood pressure (BP), and body mass index[ 36 ] confirmed the effect of theory-based intervention on clinical outcomes.…”
Section: Resultsmentioning
confidence: 95%
“…The participants with heart failure (HF),[ 26 27 28 29 30 31 32 33 ] coronary heart disease (CHD),[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] hypertension (HTN),[ 13 39 40 41 42 43 44 ] coronary artery bypass graft (CABG),[ 20 45 46 47 48 ] myocardial infarctions (MI),[ 17 19 49 50 51 ] patients with pacemaker,[ 52 ] heart valve disease,[ 53 ] and cardiac rehabilitation[ 18 ] were highest and lowest target groups in studied papers, respectively. The detailed characteristics of included studies are revealed in [ Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypertension is one of the key risk factors of atherosclerosis, stroke, and heart and kidney failure (1,2). In the last four decades, the prevalence of hypertension has reduced in high-income countries but increased in low-income countries, and is anticipated to increase by 60% to reach 1.56 billion worldwide by 2025 (3).…”
Section: Introductionmentioning
confidence: 99%